First presentation of pyoderma gangrenosum in a patient with partial immunoglobulin A deficiency. Issue 4 (April 2022) - Demirel, S; Shetty, M; Patel, M; Mahmood, K
Summary: We describe the case of a 58-year-old female with an intensely painful and rapidly enlarging necrotic cutaneous ulcer to the right shin on a background of partial immunoglobulin A deficiency (IgAD). She was seen by various healthcare professionals and managed with upscaling antibiotics for cellulitis requiring an inpatient hospital stay. The dermatology team made a clinical diagnosis of ulcerative Pyoderma Gangrenosum (PG) on assessing the patient 13 days post-onset of symptoms. The patient responded dramatically to steroids and oral tetracycline. This case highlights the unusually described association between PG and IgAD as well as the diagnostic challenge seen in patients presenting with PG.